Virtual enterprise formation and partner selection: an analysis using case studies. (7th May 2007) - Petersen, Sobah Abbas
A Virtual Enterprise (VE) can be described as an organisational form that emerges when individual entities form a team of partners to achieve a specific goal. The ability to assemble the best team is critical to the success of the VE and this imposes strong demands on its formation. In this paper, we present an agent-based model of a VE, where the partners of a VE are represented by software agents. We show how this model can support the different processes that are used in industry for selecting the partners. Industrial case studies have been used to illustrate the different partner selection processes that are used in industry. The selection processes are analysed using Agent Interaction Protocols (AIP) to describe the interactions that take place between the different entities.